(untitled) (Annals of Medical Research, 2022)
Aim: Methotrexate (MTX), a folic acid antagonist, is widely used in the treatment of many malignancies. However, various serious side effects caused by MTX limit its clinical use. Neurotoxicity is one of the most important side effects seen during MTX treatment. Oxidative damage is explained as one of the side-effect mechanisms caused by MTX. In addition to the many health benefits of fish oil (FO), its antioxidant properties have also been shown in various studies. In this study, it was aimed to investigate the potential beneficial effects of FO against oxidative brain damage caused by MTX. Materials and Methods: Twenty-eight rats were randomly divided into 4 groups (n = 7). The first group is the control group. The second group was determined as the FO group and 1000 mg / kg / day FO was given by gavage to the rats in this group for two weeks. The third group was determined as MTX group and a single dose of 20 mg / kg MTX was injected intraperitoneally to the rats in this group on the third day. The fourth group was determined as MTX + FO group, and the rats in the group were given MTX and FO in similar doses together. Results: The administration of MTX caused significant increase in TBARS levels compared to the control group, and significant decrease in SOD, GPx and CAT activities. However, the administration of FO with MTX caused statistically significant decrease in TBARS level and a significant increase in SOD and GPx activities compared to MTX group. On the other hand, there was no difference between the groups in terms of GSH levels. In addition, administration of MTX did not cause a histopathologically significant lesion in the brain tissue. Conclusion: Our results support that the use of FO may benefit against neurological oxidative damage caused by MTX.